Developing a New European Indicator of Potential Skill Shortages - Seamus McGuinness; Elisa Staffa; Sangwoo Lee; Lorcan Kelly; Paul Redmond (Institute of Labor Economics (IZA), 2025)
Skill shortages are a type of skill mismatch whereby employers are unable to fill existing vacancies due to a lack of suitably qualified and/or skilled candidates. Despite representing a significant concern for policy makers, both at national and EU level, the literature on skill shortages is hugely underdeveloped. There is a lack of clarity and consistency on how skill shortages are defined and measured. In this study, using data from the 2021 European Skills and Jobs Survey combined with Lightcast job vacancy data, we attempt to bridge the methodological gap by developing a measure of potential skill shortages that can be readily replicated across countries over time. We estimate that approximately 2% of job vacancies in the European Union are likely to experience skill shortages. However, there is substantial variation across occupations, ranging from 5.1% for ICT professionals to approximately zero in more elementary occupations. There is also substantial variation in the estimated incidences of potential skill shortages at member state level. Our analysis also shows that occupations that are most likely to experience skill shortages also tend to experience relatively high rates of changes in skill requirements over time.
Keywords: J6; J20; J22; J23; 330; skill shortages; measurement; policy